The Principles of the Voluntary Programme for the Control and Elimination of Bovine Viral Diarrhoea Virus (BVDV) From Infected Herds in Slovenia - Toplak, Ivan; Hostnik, Peter; Černe, Danijela; Mrkun, Janko; Starič, Jože (Frontiers in Veterinary Science, 2021)
In Slovenia, the control of bovine viral diarrhoea virus (BVDV) infections started in 1994. Since 2014, a voluntary programme has been running according to the national rules that prescribe the conditions for recognising, acquiring, and maintaining a BVDV-free status for an individual herd. The principle is based on periodical laboratory testing and preventive measures that need to be strictly implemented in a herd. Between 2014 and 2020, a total of 348 herds were included in BVDV antibody testing, and 25.00% of tested herds were detected to be BVDV antibody positive. For the recognition of the BVDV-free status of the herd, the breeder should provide two consecutive tests with intervals of at least six months in all animals in the age from 7 to 13 months, with negative results for BVDV antibodies in ELISA. The BVDV-free status of the herd can be maintained by implementing preventive measures and can be renewed each year with one laboratory test in the age group of animals from 7 to 13 months for antibodies in ELISA. During the seven years of the voluntary programme, 236 herds were included into the detection of BVDV in individual herds by real-time RT-PCR method and the elimination of positive animals from herds. In 71 (31.31%) herds, at least one BVDV-positive animal was detected, with the identification of a total of 267 persistently infected (PI) animals, representing an average of 2.95% of tested animals. The cost of testing for an average herd, which was recognised as BVDV-negative and was maintaining its BVDV-free status within the implemented voluntary programme, was €97.64/year, while for the average positive herd, the laboratory costs for elimination of BVDV were €189.59/year. Only limited progress towards eradication at the national level has been achieved in Slovenia in the previous seven years.